2006
DOI: 10.1111/j.1540-4560.2006.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Youth Justice in New Zealand: Restorative Justice in Practice?

Abstract: The Children, Young Persons, and Their Families Act 1989 put in place new objects, principles, and procedures for youth justice in New Zealand. Both the philosophy underpinning this system and the use of family group conferences exemplify a restorative justice approach that has now been adopted in many other countries. This article describes these changes and presents some of the results of recently published research that examines the extent to which young offenders have been diverted from courts and custody,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 1 publication
(3 reference statements)
0
60
0
Order By: Relevance
“…Community-based RJ mechanisms were promoted in order to reduce crime among members of aboriginal communities, enhance pride and coherence among such communities and empower them to find culturally specific solutions to crime and injustice (Crawford & Clear, 2001;Maxwell & Morris, 2006;Ross, 1996). Family group conferences, for instance, involve family and extended family, as well as other supporters, of each party, recognizing their crucial role in the process (Maxwell & Morris, 2006;Pennell & Burford, 2002). Sentencing circles typically involve all members of the relevant community who are invited to discuss the desired resolution for a crime committed within that society (Pranis, 2015;Tomporowski, Buck, Bargen, & Binder, 2010).…”
Section: Theorizing the Community In Rjmentioning
confidence: 99%
“…Community-based RJ mechanisms were promoted in order to reduce crime among members of aboriginal communities, enhance pride and coherence among such communities and empower them to find culturally specific solutions to crime and injustice (Crawford & Clear, 2001;Maxwell & Morris, 2006;Ross, 1996). Family group conferences, for instance, involve family and extended family, as well as other supporters, of each party, recognizing their crucial role in the process (Maxwell & Morris, 2006;Pennell & Burford, 2002). Sentencing circles typically involve all members of the relevant community who are invited to discuss the desired resolution for a crime committed within that society (Pranis, 2015;Tomporowski, Buck, Bargen, & Binder, 2010).…”
Section: Theorizing the Community In Rjmentioning
confidence: 99%
“…These forums may include community mediation, family group conferences, victimÁoffender mediations, reconciliation commissions, sentencing circles and informal tribunals Across a wide variety of offences and program types, there have been many positive outcomes from restorative justice. These include: reduced rates of re-offending (Ahmed & Braithwaite, 2006;Latimer, Dowden, & Muise, 2005;Shapland et al, 2008), higher perceptions of fairness (Braithwaite, 2002), greater satisfaction among victims and offenders (Braithwaite, 2002;Pennell, 2006;Schmid, 2003;Shapland et al, 2008), higher compliance rates among offenders (Roche, 2003), and reduced numbers of offenders progressing through the criminal justice system (Maxwell & Morris, 2006). A meta-analysis by McCold (2003) reviewed 98 restorative justice programs and 21 court samples and found that, regardless of country, clients, or program type, restorative justice programs generally performed as well or better than traditional court cases.…”
Section: Introductionmentioning
confidence: 97%
“…These would then resonate more truly with the work in each context. From that point, more specific principles would govern youth justice practices (Maxwell & Morris, 2006), and care and protection (Connolly & Ward, 2008).…”
Section: Introductionmentioning
confidence: 99%